Perancangan Sistem Informasi Monitoring Kegiatan Santri Di Pondok Pesantren Technopreneur As-Shofa Berbasis Web - Andhika, Ahmad; Samsoni (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The information regarding Pondok Pesantren Technopreneur As-Shofa has so far been exclusively conveyed to the students. The lack of communication between parents and the Islamic boarding school administration has resulted in parents not being able to monitor their children effectively. Moreover, there have been challenges in reporting violations, sharing student achievements, and managing students' memorization manually. Therefore, a web-based student activity monitoring application was developed. In the development of this application, the Unified Modeling Language (UML) was employed for system modeling, and Rapid Application Development (RAD) was used for system design. The system testing, conducted using Blackbox testing and User Acceptance Testing (UAT) methods, concluded that the student activity monitoring information system possesses an attractive interface (80%). The menus within the information system are easily comprehensible to parents (84%). Information about student activities is clear and easily understood through the application (90%). The application significantly aids parents in monitoring their child's progress (89%). The information system effectively provides sufficient details about student violations (91%), achievements (88%), and memorization progress (86%). Furthermore, the point system for violations, achievements, and memorization is seamlessly integrated into the application (87%).